Identifying Violent Behavior Using the Oxford Mental Illness and Violence Tool in a Psychiatric Ward of a German Prison Hospital - Negatsch, Vincent; Voulgaris, Alexander; Seidel, Peter; Roehle, Robert; Opitz-Welke, Annette (Frontiers in Psychiatry, 2019)
Background: Although there is evidence that individuals who suffer from severe mental disorders are at higher risk for aggressive behavior, only a minority eventually becomes violent. In 2017 Fazel et al. developed a risk calculator (Oxford Mental Illness and Violence tool; OxMIV) to identify the risk of violent crime in patients with mental disorders. For the first time, we tested the predictive validity of the OxMIV in the department of psychiatry at the prison hospital in Berlin, Germany, and presented findings from our internal validation. Material and Methods: We designed a cohort study with 474 patients aged 16-65 years old who met the inclusion criteria of schizophrenia spectrum or bipolar disorder and classified the patients into two groups: a violent group with 191 patients and a non-violent group with 283 patients. Violence was defined as the aggressive behavior of a patient with the necessity of special observation. We obtained all the required information retrospectively through patient files, applied the OxMIV tool on each subject and compared the results of both groups. Sensitivity, specificity and positive/negative predictive values were determined. We used logistic regression including variable selection and internal validation to identify relevant predictors of aggressive behavior in our cohort. Results: The OxMIV-score was significantly higher in the violent group (median 4,21%; IQR 8,51%) compared to the non-violent group (median 1,77%; IQR 2,01%; p<0,0001). For the risk of violent behavior, using the 5% cut-off for "increased-risk", the sensitivity was 44% and the specificity was 89% with a positive predictive value of 72% and a negative predictive value of 70%. Applying logistic regression, four items were statistically significant in predicting violent behavior: previous violent crime (adjusted odds ratio 5,29 [95% Cl 3,10-9,05], p<0,0001), previous drug abuse (1,80 [1,08-3,02], p=0,025) and previous alcohol abuse (1,89 [1,21-2,95], p=0,005). The item recent antidepressant treatment (0,28 [0,17-0,47], p<0,0001) had a statistically significant risk reduction effect. Conclusions: In our opinion, the risk assessment tool OxMIV succeeded in predicting violent behavior in imprisoned psychiatric patients. As a result, it may be applicable for identification of patients with special needs in a prison environment and thus, improving prison safety.